The 23rd International Electronic Conference on Synthetic Organic Chemistry 2019
DOI: 10.3390/ecsoc-23-06482
|View full text |Cite
|
Sign up to set email alerts
|

A Sonochemically-Synthesized Microporous Metal-Organic Framework for the Rapid and Efficient Ultrasonic-Assisted Removal of Mercury (II) Ions in a Water Solution and a Study of the Antibacterial Activity

Abstract: Nowadays, water pollution due to heavy metal ions is a great concern in all human communities. In this project, a metal-organic frameworks (MOFs), which were named Zn2(oba)2bpy, (1; H2oba = 4,4-oxybisbenzoic acid and bpy = 4,4-bipyridine) linkers, were successfully synthesized. The properties of these MOFs were investigated using different techniques, such as FT-IR, XRD, and SEM analysis. The frameworks have special characteristics, like the rapid, efficient, and selective removal of metal ions from contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(47 reference statements)
0
2
0
Order By: Relevance
“… 38 Agglomeration of Cu-MOF was exhibited after integration using ultrasonication. Although it was reported that ultrasonication reduced the MOF size, 39 it may cause agglomeration due to the molecular collisions of the Cu-MOF.…”
Section: Resultsmentioning
confidence: 99%
“… 38 Agglomeration of Cu-MOF was exhibited after integration using ultrasonication. Although it was reported that ultrasonication reduced the MOF size, 39 it may cause agglomeration due to the molecular collisions of the Cu-MOF.…”
Section: Resultsmentioning
confidence: 99%
“…The sonochemical synthesis of 3D microporous [Zn 2 (oba) 2 (bpy)] ( 1 ; H 2 oba = 4,4-oxybisbenzoic acid and bpy = 4,4-bipyridine) linkers has been reported by Moradi et al 86 for the development of luminescence sensors for the detection of Fe 3+ ions. The obtained photoluminescence intensity was sensitive to the type of solvent used, with MeOH showing the best performance among other solvents (ethanol, acetonitrile, THF, DMF, water).…”
Section: Synthesis Of Mofsmentioning
confidence: 99%